(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background and Objective: India has an adolescent population of 356 million, accounting for 21% of the total population of the country (1), which will form the future workforce aiding to the economic growth of the country. The fast-paced changes and evolution in the society make it imperative yet difficult for these developing young minds to adapt. Mental disorders have their onset before the age of 25 years hence, addressing the mental health needs of this population along with physical health should be primary. Neuropsychiatric disorders also add to the economic burden of the country. Focus should now be shifted more towards preventing these illnesses than intervention. This study was done to recognize the prevalence of mental and psychological problems faced by the school going adolescents aged 14-18 years using a preformed questionnaire. Method: This is a cross sectional observational study conducted over 523 subjects. The subjects were asked to fill out a preformed questionnaire from June 2019 to December 2019. Data was filled and analyzed using excel sheets and the outcome was studied. Result: Mental health problems are highly prevalent in the study population. Psychosomatic symptoms were seen in 183 students (34.9%) of the total population. Symptoms suggesting depression were reported by 146 subjects (27.9%) of a total 523. 198 students (37.8%) showed symptoms of anxiety while 127 (24.3%) depicted eating disorders. A multidimensional approach in health systems should be modelled to target adolescent mental health. Aim should be to reduce risk factors and reinforce protective factors.